On the Importance of Legal-Philosophical Thinking - Jovanović, Miodrag (Glasnik Advokatske komore Vojvodine, 2024)
The main thesis of this paper is that one can be a lawyer, even a very good lawyer, without a jurisprudential education, but that those who are educated in legal-philosophical thinking acquire an important asset that can make them better than their colleagues. In order to show this, in the first part of the paper I try to establish what it is that can be labeled a legal-philosophical thinking. In that respect, I discuss three different perspectives of that thinking, which I metaphorically - according to the names of three well-known canvases - designate as: bird’s eye view, deep gaze and anatomy lesson. In the central part of the work, I try to show the relevance of each of these three particular perspectives of legal-philosophical thinking for the profession of lawyer, by analyzing three well-known catchphrases related to that profession. Those catchphrases are: „two lawyers, three opinions“; „one is theory, the other is practice“; and, „lawyers look for legal loopholes.“ After analyzing them, in the final part of the paper I come to the conclusion that jurisprudential education develops argumentative potentials in the best way, sharpens both analytical and critical thinking, and all of this is of great use to graduated lawyers in their practice of law.